Large-area printed supercapacitor technology for low-cost domestic green energy storage - David Gethin (Energy, 2016)
In this research we demonstrate that a flexible ultra-thin supercapacitor can be fabricated using high volume screen printing process. This has enabled the sequential deposition of current collector, electrode, electrolyte materials and adhesive onto a Polyethylene terephthalate (PET) substrate in order to form flexible electrodes for reliable energy storage applications. The electrodes were based on an activated carbon ink and gel electrolyte each of which were formulated for this application. Supercapacitors that have surface areas from 100 to 1600 mm2 and an assembled device thickness of 375 μm were demonstrated. The capacitance ranged from 50 to 400 mF. Capacitance of printed carbon electrodes is rarely reported in literature and no references were found. The chemistry developed during this study displayed long-term cycling potential and demonstrated the stability of the capacitor for continued usage. The gel electrolyte developed within this work showed comparable performance to that of a liquid counterpart. This improvement resulted in the reduction in gel resistance from 90Ω to 0.5Ω. Significant reduction was observed for all resistances. The solid-state supercapacitors with the gel electrolyte showed comparable performance to the supercapacitors that used a liquid electrolyte. This large area printed device can be used in future houses for reliable green energy storage.